2014
DOI: 10.1590/s0100-06832014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de Organossolos em ambientes de várzea do nordeste do Brasil

Abstract: RESUMOOs Organossolos são geralmente associados às regiões Sudeste e Sul do Brasil, e são poucos os estudos sobre a ocorrência e os efeitos do uso e manejo agrícola desses solos na região Nordeste. Os objetivos deste trabalho foram caracterizar física, química e morfologicamente seis perfis de Organossolos de várzeas dos Estados do Ceará, Rio Grande do Norte e da Paraíba e correlacionar seus atributos ao ambiente de formação, além de quantificar seus estoques de carbono e suas capacidades de armazenamento de á… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
2
6
0
2
Order By: Relevance
“…According to D'Amore and Lynn (2002), Bd and SOM are inversely correlated in Organosols, most likely Rev Bras Cienc Solo 2016;40:e0151317 because of the low bulk density of organic matter in relation to soil mineral fractions. The inverse correlation between Bd and C content was also shown in Brazilian organic soils by Kämpf and Schneider (1989), Valladares et al (2007) and Cipriano-Silva et al (2014). Nevertheless, information on associations among C (total and/or in humic fractions), organic matter density (OMd), minimum residue (MinR), fiber content, pyrophosphate index (PyI), and the von Post index are still limited.…”
Section: Introductionmentioning
confidence: 89%
“…According to D'Amore and Lynn (2002), Bd and SOM are inversely correlated in Organosols, most likely Rev Bras Cienc Solo 2016;40:e0151317 because of the low bulk density of organic matter in relation to soil mineral fractions. The inverse correlation between Bd and C content was also shown in Brazilian organic soils by Kämpf and Schneider (1989), Valladares et al (2007) and Cipriano-Silva et al (2014). Nevertheless, information on associations among C (total and/or in humic fractions), organic matter density (OMd), minimum residue (MinR), fiber content, pyrophosphate index (PyI), and the von Post index are still limited.…”
Section: Introductionmentioning
confidence: 89%
“…The cassava presented the lowest SOM values in both methods and depths. In Histosols, Cipriano- Silva et al (2014) found values between 175 and 181 g kg -1 when cultivated with sugarcane and cassava; and Moura et al (2013) found values of 122 and 126 g kg -1 with cassava. These results indicate the effect of long period of cultivation and crop management, leading to intense SOM mineralization.…”
Section: Characterization Of the Sorption Complex Ph And Organic Matmentioning
confidence: 98%
“…The C stored in soil is composed of organic C (1500 Pg C) and mineral C (700 Pg C) (BATJES, 1996). However, the soil organic matter is easily decomposed through cropping (CIPRIANO-SILVA et al, 2014) thus aggravating the release of gases such as CO 2 (CERRI et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The lower plateaus in Northeast Brazil exhibit Cambissolos and Vertissolos derived from Jandaíra Group limestones, with pH above 7 and base saturation above 90 % (Lemos et al, 1997), as well as Organossolos (Histosols) (Silva et al, 2014). Also in Northeast Brazil, Vertissolos with high-activity clay and high contents of Ca and Mg, originating from calcareous sediments, are found in the Fernando de Noronha Archipelago, Pernambuco (Marques et al, 2014).…”
Section: Introductionmentioning
confidence: 99%